1993
DOI: 10.1080/07373939308916903
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Clay Roofing Tile Convection Drying

Abstract: Kinetics of the convection drying process of flat tile has been investigated experimentally in an industrial tunnel dryer. Several velocities of wet tile movement through the dryer were tested to obtain maximum allowable drying rate curve. As there are various models to describe the kinetics of convection drying, finding a model that would fairly well approximale the kinetics of the whole drying process was part of the research. Especially the polynomial and exponential models were tested. It was found that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We found in the literature that volumetric shrinkage of the examined wood samples is as follows: for alder up to 10.1% (Kozlik and Boone, 1987; Rasmussen, 1991) and for willow up to 13.6% (Rasmussen, 1991). Shrinkage of Ilito‐montmorilonite clay was determined by Tomas et al (1993), who found out that clay shrinks up to 6.8%, again mostly during the constant rate period (up to 6%). Vierira et al (2006) concluded that significant changes of the structural properties were verified for the paper dried at 90°C (higher than the end paper temperature dried in the microwave drier).…”
Section: Resultsmentioning
confidence: 98%
“…We found in the literature that volumetric shrinkage of the examined wood samples is as follows: for alder up to 10.1% (Kozlik and Boone, 1987; Rasmussen, 1991) and for willow up to 13.6% (Rasmussen, 1991). Shrinkage of Ilito‐montmorilonite clay was determined by Tomas et al (1993), who found out that clay shrinks up to 6.8%, again mostly during the constant rate period (up to 6%). Vierira et al (2006) concluded that significant changes of the structural properties were verified for the paper dried at 90°C (higher than the end paper temperature dried in the microwave drier).…”
Section: Resultsmentioning
confidence: 98%
“…Experimental data on these isotherms at temperature from 20 to 40°C and water activity from 0.20 to 0.70 were determined using the static gravimetric method. The experimental data were fitted by the well-known Guggenheim-Anderson and de Boer (GAB) model (Van den Berg & Bruin, 1981):…”
Section: Desorption Isothermmentioning
confidence: 99%
“…Fick's laws of diffusion and Fourier's law of conduction as well as its derived equation (e.g. Thin-layer drying equation) account for a significant proportion of the mathematical models employed in clay science (Evans and Keey, 1975;Tomas, et al, 1993;Kanno, et al, 1996;Su 1997;Sander, et al, 1998Sander, et al, , 2001Sander, et al, , 2003Moropoulou, et al, 2004Moropoulou, et al, , 2005Murugesan, et al, 2001;Mihoubi, et al, 2004;Dincer and Sahin, 2004;Akpinar and Dincer, 2005;;Chemkhi, et al, 2004Chemkhi, et al, , 2005. However, many of these models include different moisture transfer parameters that have a wide variation of reported values, depending on the complexity of the product and methods of moisture estimation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Page (1949) and Tomas et al (7) involved the exponent n, as a second parameter (5,7) for better correlation between the experimental data and the mathematical model:…”
Section: Experimental Data Analysismentioning
confidence: 99%